2002
DOI: 10.1097/00130404-200209000-00010
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Troglitazone, an Activator of the PPAR?? Receptor, in Patients with Chemotherapy-Resistant Metastatic Colorectal Cancer

Abstract: Troglitazone is not an active agent for the treatment of metastatic colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(115 citation statements)
references
References 17 publications
3
112
0
Order By: Relevance
“…122 The efficacy of troglitazone was also evaluated in 25 patients with metastatic colorectal carcinoma but all patients had progressive disease. 123 In breast cancer, two human trials have been conducted. In one study, no objective response to troglitazone after 8 weeks of treatment was observed in 22 women with refractory breast cancer.…”
Section: Safety Issues and Pparγ Agonists In Clinical Developmentmentioning
confidence: 99%
“…122 The efficacy of troglitazone was also evaluated in 25 patients with metastatic colorectal carcinoma but all patients had progressive disease. 123 In breast cancer, two human trials have been conducted. In one study, no objective response to troglitazone after 8 weeks of treatment was observed in 22 women with refractory breast cancer.…”
Section: Safety Issues and Pparγ Agonists In Clinical Developmentmentioning
confidence: 99%
“…For example, by inducing terminal differentiation in neoplasms, cancer researchers hope to stop abnormal proliferation. Tumor suppressing drugs that were created using this mechanistic understanding are currently in human clinical trials (Kulke et al 2002).…”
Section: Cancer and Embryogenesismentioning
confidence: 99%
“…[30][31][32] Consequently, the efficacy of PPAR-g ligands on a variety of nonlipogenic malignancies was tested but, unfortunately, yielded little improvement in outcome. 33,34 Thus, enthusiasm for the use of PPAR-g ligands as differentiation-promoting therapy has somewhat waned. 30 Nevertheless, our study suggests that the vast majority of dedifferentiated liposarcoma retain detectable levels of PPAR-g protein, and re-evaluation of this selected group of sarcomas with therapy targeting PPAR-g may be worthwhile.…”
Section: Discussionmentioning
confidence: 99%